2012
DOI: 10.1186/ar4055
|View full text |Cite
|
Sign up to set email alerts
|

Low sclerostin levels: a predictive marker of persistent inflammation in ankylosing spondylitis during anti-tumor necrosis factor therapy?

Abstract: IntroductionSclerostin levels have been reported to be low in ankylosing spondylitis (AS), but there is no data regarding the possible role of this Wnt inhibitor during anti-tumor necrosis factor (TNF) therapy. The present study longitudinally evaluated sclerostin levels, inflammatory markers and bone mineral density (BMD) in AS patients under anti-TNF therapy.MethodsThirty active AS patients were assessed at baseline, 6 and 12 months after anti-TNF therapy regarding clinical parameters, inflammatory markers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 35 publications
8
42
0
1
Order By: Relevance
“…Of particular note, low serum sclerostin levels in patients with AS in this study were significantly associated with the formation of new syndesmophytes. Similar findings were seen in two other cohorts of Swedish [50] and Brazilian AS patients [64]. Yet, other studies showed no differences or even demonstrated elevated levels of sclerostin comparing between AS patients and controls [46, 65, 66].…”
Section: Markers Of Radiographic Severity and Progression (Table 3)supporting
confidence: 86%
“…Of particular note, low serum sclerostin levels in patients with AS in this study were significantly associated with the formation of new syndesmophytes. Similar findings were seen in two other cohorts of Swedish [50] and Brazilian AS patients [64]. Yet, other studies showed no differences or even demonstrated elevated levels of sclerostin comparing between AS patients and controls [46, 65, 66].…”
Section: Markers Of Radiographic Severity and Progression (Table 3)supporting
confidence: 86%
“…There are reports correlating AS and decreased SOST levels 5 24. AS patients have minimal expression of SOST in osteocytes 5.…”
Section: Discussionmentioning
confidence: 99%
“…(Hamlet, William Shakespeare). [39,40] • Proteonomics [43] • Specific Biomarkers Vascular endothelium growth factor [44] Matrix metalloproteinase-3 [45,46] Sclerostin [47,48] Calprotectin [49] Citrullinated vimentin [50] Dikkopf-1 [51] Anti-CD74 antibodies [52][53][54] 56.•• van Tubergen A. The changing clinical picture and epidemiology of spondyloarthritis.…”
Section: Resultsmentioning
confidence: 98%
“…Appropriate assessment of criterion validity of the Bconstruct^axSpA would include verification of its biologic association with AS genetics, including MHC and non-MHC gene variants, and proteomic or other biomarkers that turn out to be typical for and occur frequently in classical AS. Candidate biomarkers, mostly hypothetical at this stage, are listed in Table 6 [39,40,[43][44][45][46][47][48][49][50][51][52][53][54]. Some of these biomarkers may turn out to have prognostic value, and those will be most suitable as predictors of outcome, not as candidates for classification criteria that are intended to create homogeneity, not prognostication.…”
Section: Moving Forward From Concept To Valid Criteriamentioning
confidence: 98%